Selfhood in Search of Godhood. (March 2013) - Tripathi, R.C.; Ghildyal, Prachi
The article seeks to create a space for the concept of 'self as God' in the discourse on self-psychology. It attempts to understand how the central concept of spiritual or divine self finds expression in the lives of ordinary Hindus and in their cultural practices. It is argued that Hindus seek an intimate relationship with their God and, in the process, attempt to realise divinity in self. The relationship with others, including children, teachers (Guru), nature and God is derived from this overriding idea of oneness of self and God. Some narratives of experiences of this oneness with God are given to anchor the later elaboration and analysis of this idea. Hindu rituals, the worship process, the status accorded to the Guru and to the young child (girl or boy) and even certain cases of healing and communication with family deities, as well as other deities reflect this intimacy with God. It is emphasised that the spiritual self should be seen only as one facet of self which acts in tandem with its other facets. The facet of self that assumes salience is a function of context, person's needs and life stage.